Overestimation of pretension design for uncertain cable net structures. Issue 4 (4th July 2019) - Li, Tuanjie; Zhao, Xi; Tang, Yaqiong
Abstract: When working in space environment, cable net structures suffer multisource errors including dimension errors, material parameter errors and external excitation errors. Thus, an interval force density (IFD) method was proposed for the pretension design of cable net structures under multi-errors to increase their performance robust and reliable in our previous work. However, through our further work, it is found that IFD method may lead to overestimation problem. Thus, the improved interval-truncation approach is first investigated to eliminate the overestimation problem in this article. Then, an improved IFD algorithm was put forward for the pretension design of cable net structures under multi-errors. Eventually, several numerical examples were presented and the simulation results were compared with that obtained by IFD method to demonstrate the feasibility and validity of the proposed algorithm.